Analisis Segmentasi Pasar Dalam Penggunaan Produk Viefresh Di Wilayah Sekitar Kampus Universitas Muhammadiyah Surabaya - Marta Kusuma Putri; Judith Syifa Fauziah Maria Rahman; Fatma Aulia Nursyifa; Salman Alfarisi; Tri Guntoro Sukarno Putro; Ratna Agustin (UMSurabaya Publishing, 2019)
ABSTRACT Market segmentation is an important strategy in developing marketing programs in this case the marketing of viefresh refrigerator freshener products because it can help marketers to define consumers' needs and desires appropriately. The purpose of this study was to find out how market segmentation in the area around the Muhammadiyah university campus in Surabaya in the use of viefresh products. The research design used was descriptive. The total population is 40 consumers who came to the viefresh product lauching program with a sample of 30 consumers taken by purposive sampling technique. The instrument used is a questionnaire sheet to users of viefresh products including name, age, gender, education, expenses and employment. Data analysis uses descriptive analysis with descriptive statistical tables. The results showed that the demographic segmentation of viefresh product users was mostly 18-22 years old as many as 11 people (36.67%) while based on the majority of female gender as many as 23 people (76.67%) then based on education, the majority of respondents had 12 undergraduate education people (40%) and based on monthly expenditures most of the expenditure ranges from Rp. 2,000,000 to Rp. 2,499,999.00 as many as 12 people (40%) while from the total work the respondents work as entrepreneurs 30 people (100%).Keywords : demographic segmentation, innovation products, viefresh productsCorrespondence to : khadijahfalisha@gmail.com ABSTRAK Segmentasi pasar merupakan strategi yang penting dalam mengembangkan program pemasaran dalam hal ini pemasaran produk pengharum kulkas viefresh karena dapat membantu pemasar untuk mendefinisikan kebutuhan dan keinginan konsumen secara tepat. Tujuan penelitian ini adalah untuk mengetahui bagaimana segmentasi pasar di wilayah sekitar kampus universitas muhammadiyah surabaya dalam penggunan produk viefresh. Desain penelitian yang digunakan adalah deskriptif. Jumlah populasi adalah 40 konsumen yang datang dalam acara lauching produk viefresh dengan jumlah sampel 30 konsumen yang diambil dengan teknik sampling purposive sampling. Instrumen yang digunakan adalah lembar kuesioner kepada pengguna produk viefresh meliputi nama, usia, jenis kelamin, pendidikan, pengeluaran dan pekerjaan. Analisa data menggunakan analisis dekriptif dengan tabel deskriptif statistik. Hasil penelitian menunjukkan bahwa segmentasi demografi pengguna produk viefresh sebagian besar berusia 18-22 tahun sebanyak 11 orang (36,67%) sedangkan berdasarkan jenis kelamin mayoritas perempuan sebanyak 23 orang (76,67%) kemudian berdasarkan pendidikan, mayoritas responden berpendidikan sarjana sebanyak 12 orang (40%) dan berdasarkan pengeluaran perbulan sebagian besar pengeluaran berkisar Rp 2.000.000,00-Rp 2.499.999,00 sebanyak 12 orang (40%) sedangkan dari pekerjaan seluruhnya responden bekerja sebagai wiraswasta 30 orang (100%).Kata kunci : segmentasi demografi, produk inovasi, produk viefresh,Korespondensi : khadijahfalisha@gmail.com